ISLAMIC BEAUTY: Socio-Semiotic Analysis of Facial Foam and Body Lotion Advertisement (JOURNAL OF INDONESIAN ISLAM, 2012)
This paper attempts to answer how Islamic Women define the concept of beauty in Ponds advertisement white beauty facial foam and body lotion on television. This study uses a socio-semiotic approach described through three aspects of social context, namely field, tenor, and mode. It argues that Ponds’ definition of a beauty only refers to physical standards, that is, women who have white skin and use both Ponds White Beauty Facial Foam and Foam Body Lotion. Further, television through Ponds advertising is considered as a commercial institution that supports the main idea of capitalism. However, Islamic women consider beautiful physically and spiritually. It suggests that the beautiful women are those who obey and surrender to Allah SWT. In short, Islamic women do not agree with the meaning of beauty resulted from Ponds White Beauty Facial Foam and Ponds Body Lotion advertisement. Rather, beauty consists of both body and, more importantly, soul.